Enemies are not always dear: male song sparrows adjust dear enemy effect expression in response to female fertility. (April 2017) - Moser-Purdy, Christopher; MacDougall-Shackleton, Elizabeth A.; Mennill, Daniel J.
Abstract : The dear enemy effect arises when territorial animals respond more intensely to unfamiliar strangers than to familiar neighbours. This widespread behavioural phenomenon occurs because strangers represent a threat to both an animal's territory and parentage, whereas neighbours represent a threat only to parentage. Recent research in birds demonstrates some flexibility in the dear enemy effect across the breeding season. Given that neighbours often sire extrapair young, male animals may benefit by responding more aggressively to neighbours during periods of female fertility. Here we investigate the hypothesis that the dear enemy effect varies with female fertility by testing the prediction that male birds will respond more strongly to neighbours when their own mates are fertile than when they are not fertile. We conducted a playback experiment with wild song sparrows, Melospiza melodia, repeating playback sessions to paired territorial males over the course of a breeding season, including periods when females were fertile and periods when they were not. Male song sparrows displayed a dear enemy effect only when their social mate was not fertile. We conclude that male song sparrows adjust behaviour towards neighbours based on their own mate's fertility status, presumably because neighbours threaten a territorial male's parentage during his breeding partner's fertile period. When paternity is not at stake, reduced aggression towards neighbours may enhance fitness, but when paternity is at stake, normal levels of aggression towards neighbours may be favoured as a mate-guarding tactic. Highlights: Previous studies have shown flexibility in the dear enemy effect. We hypothesized that flexibility is due to female fertility. We conducted playbacks to male song sparrows over different breeding stages. Males only displayed the dear enemy effect when their mate was not fertile. Males may respond aggressively to neighbours as a mate-guarding strategy.